The Impact of Perceived Usefulness, Perceived Ease of Use, Subjective Norm, and Experience Toward Student’s Intention to Use Internet Banking - Kevin Danurdoro; Dwi Wulandari (Universitas Negeri Malang, 2016)
The development of internet in Indonesia is quite fast and the majority of users are students. Internet growth made every fields include banking provided internet based service that called internet banking. The purpose of this research is to explore the factors that affect student’s intention to use internet banking by used the combination model of TAM (Technology Acceptance Model). Independent variables used in this research are Perceived Usefulness, Perceived Ease of Use, Subjective Norm, and Experience. While the dependent variable is Student’s Intention to Use Internet Banking. The results show that perceived ease of use and experience are significantly influence students to use internet banking and perceived usefulness and subjective norm are unsignificantly influence students to use internet banking. The usefulness of internet banking did not make the students feel interested to use internet banking, one of the reasons is usefulness of internet banking is limited to non-cash transaction Keywords: Perceived Usefulness, Perceived Ease of Use, Subjective Norm, Experience, TAM, internet banking